A new method to evaluate cross-sectional area based on computer animation of swimming - Bideau, B.; Nicolas, G.; Sanders, R. H.; Kulpa, R. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Reducing cross sectional area (CSA) during starts and turns is a key part of performance optimisation. Different methods have been used to obtain this parameter without any standard: total human body volume to the power 2/3, wetted area or frontal area based on planimetry technique (PT) (Toussaint, 1990). These different methods can lead to discrepancies in drag values (Cappaert, 1994). Recently, Nicolas et al. (2009) used two synchronized camcorders to evaluate drag parameters during the different phases of an undulatory stroke cycle. However, such a technique needs accurate synchronization and calibration of the different camcorders views. The aim of this study is to provide a new method based on animation of virtual characters to obtain instantaneous cross-sectional area in an undulatory stroke cycle. Its main advantage is to obtain cross-sectional area as well as biomechanical analysis with a single camcorder in a sagittal plan and without space calibration. METHOD: A camcorder placed side-on to the swimmer recorded the undulatory movements in the sagittal plane of eight swimmers. This information provided the angles between limbs. These data were then used by our animation engine to animate a virtual swimmer whose anthropometric data came from the real swimmer. A specific algorithm has been developed to automatically obtain the CSA using body outlines. In order to validate our method, we also calculated the CSA using PT with a frontal camcorder view of the same undulatory movements. RESULTS/ DISCUSSION: Our results show similar values of maximum CSA using PT and the frontal camcorder view (0.012±0.003m²) and our algorithm based on 3D animation (0,014±0.004m²). The mean coefficient of variation between the results obtained from the two methods is 7.3%. This difference could be related to the level of details of the mesh used to model the avatar. One prospect to this work is to take resistive and propulsive body segments into account in CSA calculation. From this method, we intend to better understand swimming hydrodynamics and the way CSA influences active drag. More generally, this approach has been designed to provide new practical insights into swimming analysis protocols.